Recycling Waste Heat from Industrial Wastewater Treatment Processes - Mc Nabola, Aonghus (My University, 2023)
Significant amounts of energy are consumed in heating water for domestic, commercial, and industrial activities. In addition, significant amounts of the energy transferred to water heating is still embedded in the wastewater discharged to the sewer and wastewater treatment systems. This paper examines the potential for wastewater heat recovery in the wastewater generated by the meat processing industry using two case study sites. Temperature monitoring at these sites showed that wastewater in the inlet of the on-site wastewater treatment plants could reach peak temperatures of up to 40°C and around 30°C on average. A pilot wastewater heat recovery system was developed and tested on-site for the potential to recover this heat using a demonstration unit that used existing technologies to directly and indirectly recover the heat in the wastewater. Initial testing showed that the largest quantity of heat recovery, up to 18.5kW using the demonstration unit’s direct heat exchange, is available in the inlet of the treatment plant; but implementing a system in this location is challenging due to the high concentration of solids present in the wastewater. Initial treatment of the wastewater with a dissolved air flotation tank reduces the solids significantly and subsequently reduces most of the operational issues at the cost of lower heat recovery. Additional testing showed that the consideration of feedwater temperatures to be heated and novel heat exchanger design are also important to consider in future work in this area.
40th IAHR World Congress
Keywords: Dissolved air flotation; Wastewater heat recovery; Drain water heat recovery; Meat processing; Smart & Sustainable Planet; HEAT TRANSFER; WASTEWATER TREATMENT